Position of Sabir Hijazi's in plays of Malakand: A Research and Critical Study - Hussain, Haider; Seemab, Sher Zaman (Makhz (Research Journal), 2024)
An exploratory review of the Dramas of Mr. Khaista Khan Sabir Hijazi. Drama is an important genre of fiction which originated from ancient Greece. It is considered to be a story composed either in prose or in poetry form to be performed with the help of characters that must have the ability to show or to stage the whole story precisely with the help of dialogues, body language or emotions. Drama is said to be a mirror or reflection of the society which portrays its real face. The Pashto literature is rich in various types of Dramas. In this article an exploratory review of the two Dramas of Mr. Khaista Khan Sabir Hijazi has been carried out.